Association analysis of TNNI1/XbaI polimorphism on carcass quality in hybrid pigs - Nyilasovits, Andrea; Posta, János; Czeglédi, Levente; Babinszky, László (Acta Agraria Debreceniensis, 2015)
The contractile protein, which is encoded by troponin I 1 (TNNI1) gene, is located on the thin filaments of slow fibres in striated muscle. TNNI1 protein is a part of the troponin complex which plays an important role in regulation of muscle contraction by preventing actin-myosin interaction in absence of calcium. According to biological role, this gene can be potential marker for meat production related traits. The aim of this study is to define whether the previously reported gene polymorphism (EU743939:g.5174T>C) is connected with the slaughter traits measured in a standard slaughterhouse of the examined four-line European hybrid. The study included data from 404 gilts and barrows from 2 different samples. The polymorphism was detected using PCR-RFLP (Polymerase Chain Reaction-Restriction Fragment Length Polymorphism) method with XbaI restriction enzyme. In this study the allele frequencies were found as follows: C: 0.84 and 0.808; T: 0.16 and 0.192. Based on result of the present study no significant impact of polymorphisms on production parameters was found.